Sosiologi Lembaga Pendidikan Sekolah Menengah Kejuruan Islam: Studi tentang Pendidikan untuk Keadilan Sosial (Sosial Justice Education) dalam Membentuk Sikap Inklusif pada Siswa di SMK Kesatrian Purwokerto - Muhammad Miftah Gunawan; Muh Hanif (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine inclusivity policies in Islamic vocational schools, analyze teachers' understanding of social justice, and examine the accountability system for inclusivity achievements. The method used was a qualitative single-case study approach at SMK Kesatrian Purwokerto. Data collection was conducted through in-depth interviews, limited participant observation, and document review. Informants were selected purposively, consisting of the vice principal for curriculum as key informants, educators, parents of children with special needs (ABK), and regular students as supporting informants. The results of the study revealed three main findings. First, inclusive policies are reactive and ceremonial because there is no written policy on anti-discrimination, so incidents are handled incidentally without structured prevention. Second, teachers' understanding of social justice is still low and uneven, characterized by handling of ABK that relies on informal information among teachers without systematic training on inclusive pedagogy. Third, there are no accountability standards to measure inclusivity achievements, considering that the education office does not require inclusivity success indicators in accreditation. This study concludes that the low effectiveness of social justice education in Islamic vocational schools is more due to systemic internal institutional weaknesses than to student resistance to diversity. Keywords: School Policy, Teacher Competency, Assessment Standards